Processing Trade, FDI and the Exports of Indigenous Firms: Firm-Level Evidence from Technology-Intensive Industries in China. - Fu, X (Blackwell Publishing, 2011)
This study examines the impact of processing trade-foreign direct investment (FDI) on the export competitiveness of indigenous firms using disaggregated firm-level production data and product-level trade data from China covering the 2000–07 period. The estimation results show that processing trade-FDI has generated significant positive information spillover effect on the export performance of indigenous firms. However, its technology spillovers effect on the development of international competitiveness in indigenous firms is limited and in fact exerts a significant depressive effect on the propensity to export in these firms. Indigenous innovation, economies of scale and productivity are found to be the main drivers of export performance in indigenous firms.